2019
DOI: 10.1021/acs.nanolett.9b01248
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Simulation, and Self-Assembly of a Model Amphiphile To Push the Limits of Block Polymer Nanopatterning

Abstract: Efforts to create block-polymer-based templates with ultrasmall domain sizes has stimulated integrated experimental and theoretical work in an effort to design and prepare self-assembled systems that can achieve unprecedented domain sizes. We recently reported the utilization of molecular dynamics simulations with transferable force fields to identify amphiphilic oligomers capable of self-assembling into ordered layered and cylindrical morphologies with sub-3 nm domain sizes. Motivated by these predictions, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 52 publications
1
34
0
Order By: Relevance
“…In our previous investigations, we have found that oligosaccharides are useful building blocks for designing BCPs capable of self-assembling into microphase-separated structures of sub-10 nm domain size [36][37][38][39][40][41]. In these systems, the strong hydrophilicity imparted by the presence of multiple hydroxyl groups results in oligosaccharide-containing amphiphilic BCPs with high χ values, and the rigidity of the carbohydrate backbone further enhances the incompatibility of the hydrophilic block with the hydrophobic block.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous investigations, we have found that oligosaccharides are useful building blocks for designing BCPs capable of self-assembling into microphase-separated structures of sub-10 nm domain size [36][37][38][39][40][41]. In these systems, the strong hydrophilicity imparted by the presence of multiple hydroxyl groups results in oligosaccharide-containing amphiphilic BCPs with high χ values, and the rigidity of the carbohydrate backbone further enhances the incompatibility of the hydrophilic block with the hydrophobic block.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, strong segregation between hydrophilic saccharidic blocks and hydrophobic isoprene-based hydrocarbon chains would be expected, which would in turn allow microphase separation in the molecular-weight regime below 2000 g mol −1 . In addition, recent reports [33][34][35] by Lodge, Siepmann, and Hillmyer on sugarbased amphiphiles with a hydrocarbon chain, leading to a lamellar morphology with d of 3.5 nm (even down to d of 1.2 nm as revealed by molecular dynamic simulation), also supports that the combination of sugars and terpenoids is highly promising for realizing ultrasmall nanostructure formation. More importantly, oligosaccharide and terpenoid blocks showing defined and discrete degrees of polymerization (DPs) are commercially available, and a series of BCOs featuring monodispersity and discrete DPs can be synthesized readily from them, providing rapid access to various ultrasmall nanostructures showing diverse morphologies, features, and sizes.…”
mentioning
confidence: 59%
“…(580-964 g mol −1 ) and total DP (4-6) ( Table 1). Such an ultrasmall d value of 4 nm has rarely been reported among the organic-BCP-derived LAM microphase-separated structures 9,14,23,31,34,47 . Given the f sugar of Glc 1 -b-Far, the sugar microdomain thickness is approximately 1.2 nm, which shows promise to ultrahigh-resolution nanofabrication.…”
Section: Synthesismentioning
confidence: 87%
“…Although, as pointed out by Kim et al additional challenges such as selectivity of etching or density of patterns [211] still need to be controlled and further improved; BCPL can already overcome limitations of conventional photo-, beam-, and soft lithography, and it can not only produce sub-10 nm scale features [26,214,217,219,225], but it can also lead to the fabrication of sub-5 nm relief patterns [196,199,213,226] (Figure 12a). In the future, this could be further improved as theory simulations predict the possibility to access sub-2 nm domains when employing the self-assembly of model amphiphiles [227] or even 1 nm-sized domains when making use of oligomers [228] (Figure 12b). Nonetheless, this high lateral resolution might come often with challenges such as mechanical stability [196].…”
Section: Block Copolymer Lithography Based On (Directed) Self-assemblymentioning
confidence: 99%